"Sebuah Kontestasi Stratifikasi Dominasi Dalam Kapitalisme dan Konsumerisme" (Dalam Perspektif Teori Sosio HistorisKritis C. Wright Mills) - Prananta, Arie Wahyu (DIMENSI, 2015)
Study and Discussion Middle Class in Indonesia Since the 1970s making us Startled andremind them a very central role in the class structure of the elite class and the lower class.Mengah class structure that is very dynamic and became the most influential class in the classstructure Indonesia1 nation. The most influential class of bargaining structure makes itdifficult to track class in the class structure of the Indonesian nation but their role is veryimportant, and some of the events changes ranging from the collapse of the old order and thenew order and the new order to the order of the reform to make the lesson for the nation thatetintas and their role is to make the power of change in the state system and social structure inthe community. Vagueness figure mengah class in the social structure in the community makethis a decent middle-class researched and chosen as a topic there does require quite a lot ofstudy and also an imagination in soiologi to be in perspektifkan and projected in an empiricalobject assumes constructed reality of objects material to be appointed as a more macroassumptions preposition. The existence of vague mengah class does not mean the absence ofmiddle class structures etintas them, the emergence of class roles mengah be a force of changein a country makes them very central role, classification and categorization within a socialstructure in the community is very vague, so the need to study very deep study and empiricallyfocused on middle-class structure, Refine concepts in a theory of the middle class by ArielHariyanto in a study Robinson is the middle class are some government officials,practitioners, managers in a company fund or class of educated intellectual, in the structureexisting social Indonesian nation. Capitalism here as in imagine a production order in thecapital penguasaaan. The need for this level of precision and mapping of capitalism in theframe in the ownership of capital